Playing by the rules of the game: partisan use of recall referendums in Colombia. Issue 8 (17th November 2018) - Welp, Yanina; Milanese, Juan Pablo
ABSTRACT: As a bottom-up mechanism of direct democracy, recall can be triggered by citizens to remove elected officials through a vote, which is expected to increase accountability. Contradicting this hope, previous research has suggested that intensive use of recall referendums became an instrument of party competition. However, empirical evidence is scant. Thus, focusing on the 107 attempts of activating recall in Colombia during the first half of 2017 this article seeks to understand if recall activations are more likely to reinforce democratic governance (by giving an institutional solution to exceptional problems of legitimacy) or are more likely to erode it (by becoming a weapon to escalate the partisan competition beyond regular elections). We created a dataset to identify who started the recall – partisan, mixed or civil society actors – and for what reasons. Then, we examined to what extent the effective number of parties in the council, the majority reached in the previous election, or the size of the municipality have an effect on the likelihood of recall attempts. The study finds that in Colombia, political leaders (and not specific parties) are the main actors promoting recall.